The role of intellectual property on Enterprise-led Industry-University-Research Institution cooperation: case of innovation awards in China - Lingzhi Chen; Yanyan Ma; Yutao Sun (Humanities & Social Sciences Communications)
Abstract The Enterprise-led Industry-University-Research Institution (E-IUR) cooperation innovation system is an integral component of the National Innovation System (NIS). This article explores the impact of intellectual property (IP) protection policies on E-IUR cooperation. Utilizing the achievement of prestigious innovation awards, this article analyzes the degree of E-IUR cooperation reflected in the ranking of the winning organizations, showcasing the position of the enterprises program in high-level technological innovation in China and the leadership among E-IUR cooperation. Additionally, this paper further explores the impact of intellectual property demonstration cities (IPDC) policy on E-IUR cooperation using a difference-in-differences (DID) regression model. The study focuses on listed companies in Shanghai and Shenzhen from 2008 to 2020. The results show that IPDC policy offers significant assistance in boosting the deep integration of E-IUR cooperation. Furthermore, refining the fundamental institution of IP protection has the potential to propel the prevalence of E-IUR cooperation. The IPDC policy has strengthened the deep integration of E-IUR cooperation by increasing enterprise innovation investment and regional IP law enforcement. This study investigates the dominant-subordinate relationship among multiple innovation organizations in IUR cooperation, measures the dominant degree of enterprises in IUR cooperation compared with universities and research institutions. And we empirically test the influence of IP on the deep integration of E-IUR cooperation, which provides a direction for optimizing the IP basic system and improving the overall efficiency of NIS and RIS in emerging economies.